2004
DOI: 10.1097/01.ta.0000145076.05111.e1
|View full text |Cite
|
Sign up to set email alerts
|

The Tip of the Iceberg for Child Abuse: The Critical Roles of the Pediatric Trauma Service and its Registry

Abstract: Significant characteristics of the abused children in this pediatric trauma service include higher Injury Severity Score (especially in the head and integument), requirement for longer lengths of stay, and a nearly 10-times higher risk of death compared with the ED population. The Diagnostic Index for Physical Child Abuse is proposed as a new tool to assist in the identification of child abuse among pediatric trauma patients. An epidemiologic triangle for child abuse is described, with different prevalence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 6 publications
8
58
0
13
Order By: Relevance
“…In total, 2.3% of all children in the TARNlet study were recorded as injured because of physical abuse, but this rose to 23.5% for infants ( Table 8). 75 Similar trends were reported by Chang et al 98 In summary, we found no direct evidence that age is predictive of physical abuse in all injured children attending A&E, but admission with severe injury in infancy was moderately predictive of abuse.…”
Section: Review Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…In total, 2.3% of all children in the TARNlet study were recorded as injured because of physical abuse, but this rose to 23.5% for infants ( Table 8). 75 Similar trends were reported by Chang et al 98 In summary, we found no direct evidence that age is predictive of physical abuse in all injured children attending A&E, but admission with severe injury in infancy was moderately predictive of abuse.…”
Section: Review Resultssupporting
confidence: 77%
“…Only one study, 101 conducted in Hawaii, was based on all injured children attending A&E. Two other studies 75,98 were based on a subset of children admitted with severe injuries.…”
Section: Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4,19 Hospital discharge databases using ICD-9 codes allow the use of E-codes for assault to better identify cases of inflicted injury and injury severity scoring to judge the seriousness of the child' s abuse. 12,13,24 Our study population was limited to children 0 through 3 years of age because this represents the age group most likely to require hospitalization for injury from abuse. 18,19 Limiting the study population to the youngest age group also minimizes the potential confounder of an E-code for assault representing peer on peer violence in older age groups instead of injury perpetrated by a person responsible for the child' s care although serious injury can occur to young children by their siblings.…”
Section: Discussionmentioning
confidence: 99%